Assessment of genetic variability, correlation and path analysis studies incabbage (Brassica oleracea) under low hill conditions of Himachal Pradesh - SHARMA, PALLAVI; SINGH, SHIV PRATAP; DOGRA, B S; RANI, RIYA; VERMA, ANJALI (The Indian Journal of Agricultural Sciences, 2023)
Cabbage is economically important crop among many sectors. Twelve genotypes were evaluated during September to February (2021–22) at the College of Horticulture and Forestry (Dr Yaswant Singh Parmar University of Horticulture and Forestry), Neri, Hamirpur, Himachal Pradesh to study variability in yield and its contributing characters. In variability parameters, high GCV and PCV value indicating the considerable amount of variation was present in germplasm. High heritability with high genetic advance observed for traits, viz. days to head formation, plant height, ascorbic acid and dry matter content showed the influence of additive gene action and are highly able to transfer from one generation to other generation. Thus, selection would be effective for improvement in these genotypes. Correlation coefficient and path coefficient analysis showed that leaf breadth, gross head weight, plant frame, polar diameter, leaf size; these traits can help in evolving genotypes with higher net head weight through selection. Hence, CAB-COHF-NERI-10 and Pusa Mukta were high in yield and can be used for further breeding programme.